Estimation of Blood Sirolimus Concentration Based on Tacrolimus Concentration/Dose Normalized by Body Weight Ratio in Lung Transplant Patients. Issue 5 (October 2019) - Kikuchi, Masafumi; Shigeta, Kensuke; Tanaka, Masaki; Takasaki, Shinya; Akiba, Miki; Oishi, Hisashi; Sado, Tetsu; Matsuda, Yasushi; Noda, Masafumi; Okada, Yoshinori; Mano, Nariyasu; Yamaguchi, Hiroaki
Abstract : Background: Sirolimus and tacrolimus require accurate drug dosing based on their target blood levels to produce better clinical outcomes, specifically, the avoidance of drug-induced adverse effects and the maintenance of efficacy. However, because the ideal dose of sirolimus and the schedule for measuring its blood levels are unclear in lung transplant patients, an index is required for estimating sirolimus blood concentrations. The aim of this work is to study the correlation between the trough concentration/dose normalized by body weight (C0 /D) ratios of sirolimus and tacrolimus in lung transplant patients. Methods: Thirteen lymphangiomyomatosis patients who underwent lung transplantation and were treated with sirolimus and tacrolimus from February 2015 to July 2018 were divided into 2 groups, one receiving twice-daily (TD, n = 6) and the other once-daily (OD, n = 7) tacrolimus formulations. The correlation between the C0 /D ratio of sirolimus and patient background was evaluated using Spearman's rank correlation coefficient. Correlations between sirolimus and tacrolimus C0 /D ratios or doses were analyzed by single regression analysis. Results: Significant correlations were found between the C0 /D ratios of sirolimus and tacrolimus. The regression equations from the initial data of TD and OD groups at steady state were y = 1.880x + 32.636 (adjusted R 2 = 0.743, P = 0.017) and y = 1.684x + 38.816 (adjusted R 2 = 0.919, P < 0.001), respectively. In addition, the regression equations from all data of TD and OD groups were y = 1.883x + 4.170 (adjusted R 2 = 0.546, P < 0.001) and y = 1.950x + 43.188 (adjusted R 2 = 0.898, P < 0.001), respectively. A significant correlation between the dosage of sirolimus and tacrolimus was observed only in the OD group, with relatively low accuracy. Conclusions: Blood sirolimus concentrations can be estimated using the C0 /D ratio of tacrolimus, suggesting that the C0 /D ratio of tacrolimus is an index of required sirolimus dosage and the frequency of blood sirolimus concentration measurements.